2021
DOI: 10.3389/fphys.2021.679232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise-Induced Reductions in Blood Volume on Cardiac Output and Oxygen Transport Capacity

Abstract: We wanted to demonstrate the relationship between blood volume, cardiac size, cardiac output and maximum oxygen uptake (V.O2max) and to quantify blood volume shifts during exercise and their impact on oxygen transport. Twenty-four healthy, non-smoking, heterogeneously trained male participants (27 ± 4.6 years) performed incremental cycle ergometer tests to determine V.O2max and changes in blood volume and cardiac output. Cardiac output was determined by an inert gas rebreathing procedure. Heart dimensions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 51 publications
1
31
1
1
Order By: Relevance
“…Since the SV is also largely determined by blood volume [27,62], it is possible that an increase in SV after SP supplementation results from an increase in PV caused by an increase in serum sodium concentration [63,64]. During our experiment, blood sodium concentration was not determined.…”
Section: Discussionmentioning
confidence: 98%
“…Since the SV is also largely determined by blood volume [27,62], it is possible that an increase in SV after SP supplementation results from an increase in PV caused by an increase in serum sodium concentration [63,64]. During our experiment, blood sodium concentration was not determined.…”
Section: Discussionmentioning
confidence: 98%
“…However, this regression equation was restricted to children with sufficient iron stores and oxygen saturation >75% (21). Based on the theory of an inverse relationship between the severity of compensatory erythrocytosis and resting oxygen saturation (14) and the estimation formula of CaO 2 (18), we presumed that the value of preoperative Hb × SpO 2 can evaluate whether cyanotic children achieved adequate Hb compensation. If the value of preoperative Hb × SpO 2 of cyanotic children was below the lower limit of normal Hb of each age group, this indicated that the preoperative Hb concentration was not sufficient to obtain similar CaO 2 to healthy children, and preoperative anemia would be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Physically dissolved oxygen is rare, and noninvasive SpO 2 could replace invasive arterial oxygen saturation (SaO 2 ) tests (18), so the arterial oxygen content (CaO 2 ) for blood with normal Hb quality could be estimated according to the formula: CaO 2 (ml/dl) = 1.39(ml/g)×Hb(g/dl)×SpO 2 (%)÷100 (a)…”
Section: Mathematical Model For Integrating Hemoglobin and Oxygen Saturationmentioning
confidence: 99%
“…Recent data from Durand et al (Durand et al, 2020 ) found that athletes with EIAH had higher PAPs than similarly trained athletes without EIAH, further supporting a hemodynamic initiating mechanism of EIAH in this cohort. Additionally, Schierbauer and colleagues found that, when corrected for body mass, maximal Q̇ C , but not V̇O 2max , was correlated with the decline in S p O 2 from rest to maximal exercise ( Schierbauer et al, ). It is possible that the highly trained subjects in our study approached maximal Q̇ C values meeting or, more likely, exceeding 30–35 L·min −1 (Table 1 ) (Zhou et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be exacerbated by the considerably larger Q̇ C values of trained athletes (Ekblom & Hermansen, 1968 ; Zhou et al, 2001 ), and it has been demonstrated that intense exercise can cause stress failure of the BGB in this population (Hopkins et al, 1997 ). Indeed, recent data demonstrated that, when corrected for body mass, maximal Q̇ C , but not V̇O 2max , was correlated with the decline in S p O 2 from rest to maximal exercise ( Schierbauer et al, ). These observations suggest that extravascular fluid may accumulate in the interstitium of the lung, at least transiently, enough so that decreases in S a O 2 during exercise are evident until the pulmonary lymphatics can clear the interstitial space of the excess fluid post‐exercise (McKenzie et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%